CUT OFF VALUE OF PROCALCITONIN IN END STAGE RENAL DISEASE PATIENTS WITHOUT INFECTION (Pakistan Journal of Kidney Diseases, 2021)
OBJECTIVE:To determine cut off value of procalciton (PCT) in aseptic end stage renal disease patients undergoing haemodialysis.BACKGROUND:Haemodialysisis considered as a proinflammatory state and therefore associated with release of inflammatory cytokines and acute phase reactant proteins. The conventional laboratory markers (C-reactive protein, erythrocyte sedimentation rate) are efficient tools for the diagnosis of infection in patients with normal kidney functions. However they can be nonspecifically elevated in patients on haemodialysis and only reflect inflammatory response not associated with infection. PCT is considered a very important biomarker in differentiating infections from inflammation. The study was undertaken to evaluate normal serum levels of PCT in patients undergoing HD.PATIENTS AND METHOD: The study included 82 end-stage renal failure patients without evidence of systemic or localized infection undergoing maintenance haemodialysis.RESULTS: In our study, the PCT concentrations showed a mean of .622ng/ml in patients on maintenance hemodialysis without signs of infection.CONCLUSION:The study suggests that serum PCT at a cutoff value of .62ng/ml should be considered normal in aseptic haemodialysis patients.KEYWORDS: Procalcitonin, haemodialysis, sepsis
Keywords: procalcitonin; haemodialysis; sepsis